Ponatinib after failure of second‐generation tyrosine kinase inhibitor in resistant chronic‐phase chronic myeloid leukemia. Issue 11 (30th August 2022) - Kantarjian, Hagop M.; Jabbour, Elias; Deininger, Michael; Abruzzese, Elisabetta; Apperley, Jane; Cortes, Jorge; Chuah, Charles; DeAngelo, Daniel J.; DiPersio, John; Hochhaus, Andreas; Lipton, Jeffrey; Nicolini, Franck E.; et al.
Abstract: Ponatinib, the only third‐generation pan‐BCR::ABL1 inhibitor with activity against all known BCR::ABL1 mutations including T315I, has demonstrated deep and durable responses in patients with chronic‐phase chronic myeloid leukemia (CP‐CML) resistant to prior second‐generation (2G) TKI treatment. We present efficacy and safety outcomes from the Ponatinib Philadelphia chromosome–positive acute lymphoblastic leukemia (Ph+ ALL) and CML Evaluation (PACE) and Optimizing Ponatinib Treatment in CP‐CML (OPTIC) trials for this patient population. PACE (NCT01207440) evaluated ponatinib 45 mg/day in CML patients with resistance to prior TKI or T315I. In OPTIC (NCT02467270), patients with CP‐CML and resistance to ≥2 prior TKIs or T315I receiving 45 or 30 mg/day reduced their doses to 15 mg/day upon achieving ≤1% BCR::ABL1 IS or received 15 mg/day continuously. Efficacy and safety outcomes from patients with CP‐CML treated with ≥1 2G TKI (PACE, n = 257) and OPTIC ( n = 93), 45‐mg starting dose cohort, were analyzed for BCR::ABL1 IS response rates, overall survival (OS), progression‐free survival (PFS), and safety. By 24 months, the percentages of patients with ≤1% BCR::ABL1 IS response, PFS, and OS were 46%, 68%, and 85%, respectively, in PACE and 57%, 80%, and 91%, respectively, in OPTIC. Serious treatment‐emergent adverse events and serious treatment‐emergent arterial occlusive event rates were 63% and 18% in PACE and 34% and 4% in OPTIC. Ponatinib shows high response rates and robust survival outcomes in patients whose disease failed prior to 2G TKIs, including patients with T315I mutation. The response‐based dosing in OPTIC led to improved safety and similar efficacy outcomes compared with PACE. Abstract : Analysis of the largest CP‐CML population in a post‐second‐generation TKI setting ( N = 350)